LAND SUITABILITY EVALUATION OF SOYBEAN AS DROUGHT ADAPTATION IN GROBOGAN REGENCY - Dwi Partini (GeoEco, 2020)
Grobogan regency is a regency in central java which getting a lot of drought in dry season. The drought has an impact on various sectors of life, including agriculture. This research aims to measure the land suitability for soybean in Grobogan as an adaptation to drought season. This research is in descriptive qualitative, using purposive sampling technique to get soil sample based on the type of soil. Data collection techniques were observation, interviews, laboratory analysis.  Analysis of land suitability for soybean plants by matching the quality and characteristics of land in Grobogan Regency with the conditions for growing soybean plants. The result of this study is (1) the actual land suitability for soybean plants in Grobogan Regency shows a marginal appropriate class (S3) covering 85024.98 ha or 43.03%, not suitable (N1) covering 4792,925 ha or 2.43% and not permanently suitable (N2) covering 1896.49 ha or 0.96%. (2) Through improving the quality of land characteristics to the management of a high level of land suitability, potential can reach a sufficiently suitable class (S2) covering an area of 85248.10 ha or 43.14%, marginal appropriate (S3) covering an area of 3824.37 ha or 1.94% and not suitable (N1) totaling 2641.92 ha or 1.34% .